PENGARUH PELATIHAN PEMBUATAN MEDIA CETAK KESEHATAN LINGKUNGAN TERHADAP PENGETAHUAN DAN KETERAMPILAN MAHASISWA UKM PLAKAT JURUSAN KESEHATAN MASYARAKAT UNSOED - Kurniawan, Arif; Gamelia, Elviera; Widiyanto, Agnes Fitria (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2014)
ABSTRACT Department of Public Health student was a prospective primary of health promotor personnel in the Ministry of Health. However, students also have some disadvantages are the lack of skills in the manufacture of printed media are required in health education activities are conducted. So it is necessary to study the effect of making health printed media training for knowledge and skills in the student of UKM Plakat Department of Public Health. This research used quasi experimental study one group pre test and post test design with 25 sample of student in UKM Plakat. Analysis of the data used descriptive test results of pre test and post test. Observed variables are environmental health knowledge, knowledge of media development and media production skills. The results of the study on the comparison of pre and post test average value of environmental health knowledge increased by 14,2%, mean score of knowledge development of the printed media has increased by 11,7% and average value of media-making skills increased by 5,5%. In accordance with the results are advisable to undertake the training of other media such as manufacture of electronic media or radio spot to improving student resource in health promotion. Keywords : knowledge, health promotor, student. Kesmasindo, Volume 7(1) Juli 2014, Hal 39-45